Political Ideology Shapes Consumer Responses to Addictive Products - Ilicic, Jasmina; Brennan, Stacey (Journal of Marketing, 2026)
Consumption of addictive products, such as gambling, alcohol, tobacco, gaming, fast food, and illicit drugs, is an important public health and policy issue. Research identifies that political ideology influences positive consumer behaviors, but little is known about whether political ideology shapes negative consumer behavior. Through a ten-study multimethod investigation including a large correlational study, a field study, and eight online studies (including six experiments), the authors reveal the relationship between political ideology and consumer responses to addictive products. Results indicate that political conservatism, as opposed to liberalism, is associated with more favorable consumer attitudes, intentions, and behavior toward addictive products, due to a stronger sense of agency, which reduces perceptions of product danger. The findings show that the positive relationship between political conservatism, sense of agency, perceived product danger, and subsequent responses to addictive products can be attenuated through exposure to personally directed threat appeals (i.e., threat messages with second-person pronouns). This research advances political ideology research in marketing by demonstrating how political ideology shapes responses to addictive products and provides practical ways to shift its potential harmful effects.